Fiscal Institutions in New Zealand and the Question of a Spending Cap - Tracy Mears; Gary Blick; Tim Hampton; John Janssen (New Zealand Government, The Treasury, 2010)
New Zealand's fiscal policy framework has been in place for nearly 20 years. At its core is a set of principles around maintaining prudent levels of public debt and running fiscal surpluses on average over time. This framework, combined with an extended period of economic growth, contributed to New Zealand entering the economic recession of 2008-2009 with historically and internationally low levels of public debt. While the current fiscal policy framework has helped achieve and maintain defined, prudent levels of public debt, it does not require the government to define a target level for spending. Since 2004 government spending has increased as a share of GDP. Most of this reflects increased spending during the extended economic upturn through the middle of the last decade. The economic recession of 2008-2009 also played a small role in increasing spending, largely through the automatic stabilisers as New Zealand did not implement a substantive expenditure-based stimulus package. The Government therefore committed to investigating whether a spending cap would be an appropriate addition to the existing fiscal policy framework. This paper outlines the motivation for a spending cap and – drawing on international experience – presents a proposed design. A benefit of the proposed cap is that it would have reinforced the existing limit on new discretionary spending initiatives through the annual Operating Allowance being fixed at 1.1 billion. It would also have placed a limit on other forecast expense increases that occur via the six-monthly Baseline Update process. However, the complexity of the proposal may have led to significant communication challenges, and some confusion about how it would operate alongside the existing system. Reflecting on this analysis, the Government decided not to introduce a formal cap on total spending at Budget 2010.
Keywords: E62; H61; 330; Budget management; fiscal institutions; fiscal management approach; fiscal performance; fiscal policy; Fiscal Responsibility Act; fiscal rules; government expenses; New Zealand Government; Public Finance Act; spending cap; Finanzpolitik; Regelbindung versus Diskretion; Wirkungsanalyse; Neuseeland